A Review of Salvinorin Analogs and their Kappa-Opioid Receptor Activity - Roach, Jeremy J. (Bioorg Med Chem Lett, 2018)
The plant metabolite salvinorin A potently and selectively agonizes the human kappa-opioid receptor, an emerging target for next-generation analgesics. Here we review analogs of the salvinorin chemotype and their effects on selectivity, affinity and potency. Extensive peripheral modifications using isolated salvinorin A have delivered a trove of SAR information. More deep-seated changes are now possible by advances in chemical synthesis.